Kosovo : Health Financing Reform Study - World Bank (Washington, DC, 2012)
The objective of this report is to present information on the different health financing reform options available to Kosovo, which can help the government to make informed policy decisions about financing reforms. The report focuses on the key insurance functions of revenue collection and management, risk pooling, and purchasing of health care, as well as the supportive regulatory and governance framework for health financing. Kosovo aims to reform health financing by moving toward a health insurance system. To implement the proposed single insurer as described in the health law, a draft law for health insurance was discussed in Parliament in 2004. The draft law envisioned the revenue sources for the future health insurance as follows: (i) 60 percent of Health Insurance Fund (HIF) revenue will be paid by the general budget; (ii) 13.5 percent will come from payroll contributions; (iii) 21 percent will come from direct payments by patients in the form of user fees; and (iv) 6.5 percent will come from patients' co-payments. Three years later, in April 2007, the Kosovo Parliament approved a health insurance law to introduce social health insurance (SHI) financed predominantly through payroll taxes, though it did not specify contribution levels. The revenue potential of such payroll funded insurance was estimated to be modest considering Kosovo's relatively small formal sector and employment rate. The Kosovo health system is predominantly tax funded. Government health spending is about 3 percent of gross domestic product (GDP) and 10 percent of general government expenditures. The ministry of economics and finance (MEF) transfer's health funds from the central budget to hospitals (51 percent), to municipalities in the form of an earmarked health grant for the provision of primary health care (PHC) services (26 percent), and to the ministry of health (MOH) for other services (22 percent) (MEF 2007).